The Development of Geo-Math Application by Integrating Geo-Gebra Applets to Improve Students’ Spatial Ability - Ikhsan, M.; Rochaminah, Sutji; Mastura, Ayu (Jurnal Ilmiah Peuradeun, 2024)
Geometry can be challenging for students due to its abstract nature; The difficulty is often associated with low spatial abilities; to overcome these challenges, educators can employ dynamic and visual learning approaches to help students learn and understand geometric concepts more effectively. This study aimed to develop a Geo Math application by integrating the GeoGebra applets on geometry that fulfill valid, practical, and effective aspects that are expected to improve spatial abilities. This research utilized development research using the ADDIE model, which consists of 5 stages: analysis, design, development, and trial implementation. It went through several trial stages consisting of validation experts, one-to-one trials, and small group trials, and the evaluation stage was carried out through a pre-post-test quasi-experimental study. Based on the results, it can be concluded that the Geo Math application was very feasible to support the implementation of learning mathematics, especially in learning geometric transformations, which could assist students in constructing concepts from various transformations effectively. The interactive and dynamic nature of GeoGebra applets within the application allowed students to visualize and manipulate geometric objects and could make abstract mathematical concepts more concrete and accessible, which could improve students’ spatial abilities.